Enhancing the Quality of Learning through Changes in Students’ Approach to Learning - Md. Asad Ali; Aejaz Masih (International Journal of Asian Education, 2021)
Learning causes relatively a permanent change in one's behavior. There are multiple paradigms in the theories of learning, the latest theory in this group being Constructivism. This particular theory postulates that a learner himself/herself constructs his/her learning through an active and consistent engagement. This theory also brings the learning process to the center, where the concerned learner's prior experience is used as the base for future learning. Although quality learning is the global agenda in the 21st century, there is still no clear and concise definition. Quality of learning has diverse connotations. Researchers in this area search for it in its process as well as in its product. However, one may say the quality learning process motivates a student to have a deep engagement with the learning task possible through some suitable strategies. Kevin Warburton (2009) identified three main factors that greatly impact a student's motivation, leading to high or low engagement in the learning activity. A conducive learning environment, sophisticated course content, and favorable individual factors could enhance the student's motivation and make him/her have a deep engagement in the learning activity. The product of quality learning is measured by the nature and versatility of the learning outcome. The learning, which is extensive, integrative, and generative, may fulfill the rising demand for quality of learning.